Membrane technology for valorization of mango peel extracts - Macedo, Antónia (2022)
Mango peel is rich in nutritional and functional compounds, such as carbohydrates, dietary fibers, proteins, and phenolic compounds, with high potential to be applied in the food industry. Most of the investigation about recovery of bioactive compounds from fruit bioproducts involves extraction techniques and further separation of target compounds. There is still a lack of information about the potential of membrane processes to recover the nutritive/functional compounds present in aqueous extracts of those bioproducts. This research is addressed to study the performance of ultrafiltration (UF), followed by nanofiltration (NF) of UF permeates, to fractionate the compounds present in aqueous extracts of mango peel. Both UF and NF concentration processes were carried up to a volume concentration factor of 2.0. Membranes with molecular weight cut-offs of 25 kDa and 130 Da were used in the UF and NF steps, respectively. UF and NF concentrates showed antioxidant activity, attributed to the presence of phenolic compounds, with rejections of about 75% and 98.8%, respectively. UF membranes totally rejected the higher molecular weight compounds, and NF membranes almost totally concentrated the fermentable monosaccharides and disaccharides. Therefore, it is envisaged that NF concentrates can be utilized by the food industry or for bioenergy production.